Changes in Incidence and Survival by Decade of Patients With Primary Colorectal Lymphoma: A SEER Analysis - Qingguo Li; Qingguo Li; Shaobo Mo; Shaobo Mo; Weixing Dai; Weixing Dai; Yaqi Li; Yaqi Li; Ye Xu; Ye Xu; Xinxiang Li; Xinxiang Li; et al. (Frontiers Media S.A., 2020)
Purpose: To reveal changes in the incidence, treatment, and survival of patients with colorectal lymphoma.Methods: Patients diagnosed with primary colorectal lymphoma (PCL) or lymphoma between 1973 and 2014 were identified in the SEER registry. The incidence was estimated by age and join-point analysis. The incidence of different subtypes and the surgical resection rates were compared over different time periods.Results: The PCL incidence increased from 1.4 per 1 000 000 people in 1973 to 3.5 in 2014, with an annual percentage change (APC) of 1.98% (95% confidence interval [CI]: 1.29-2.68%, P < 0.001) from 1985 to 2014. No statistically significant change was found between 1973 and 1984. For people younger than 60 years, there was a slight increase in PCL incidence, from 0.6 to 1.4%, from 1973 to 2014. For people age 60 or older, there was a statistically significant increase in PCL incidence from 5.4 to 14.1% over the same time period. The 5-year cause-specific survival (CSS) for PCL improved markedly from 41.6% in the period 1973-1976 to 80.2% in the period 2009-2012 (P < 0.001). Conversely, the proportion of patients who received surgical therapy decreased gradually from 83.3-100 to 47.7-52.6% throughout the studied time period.Conclusions: The incidence of PLC has increased in recent decades. The 5-year CSS of PCL increased continuously, while the rate of surgical resection decreased steadily. These changes in survival trends and therapy strategies indicate that PCL can be well-managed with newer therapeutic reagents.